Implementation Of Poverty Reduction Policies By The Regional Poverty Reduction Coordination Team (TKPKD) in West Pasaman District - Winari, Sonda; Adnan, M. Fachri (International Journal of Marine Engineering Innovation and Research, 2024)
This research is based on the need to accelerate poverty reduction for community welfare. The aim of this research is to describe the implementation of poverty reduction policies by TKPKD West Pasaman Regency. This research uses qualitative research. The research location was at the West Pasaman Social Service office, the Regional Development Planning Agency (Bappeda), as well as poor villages and community leaders in West Pasaman Regency. Data collection techniques include interviews, documentation studies and field notes. The data validation technique used is a triangulation technique which involves re-checking data previously obtained from various sources to assess the correctness of the data. The data analysis procedure is broken down into several processes which include data collection, data reduction, data presentation, as well as drawing conclusions and verification. The research results show that poverty reduction by West Pasaman Regency TKPKD has not fully achieved the desired targets. There are several factors that influence the implementation of poverty reduction policies by West Pasaman Regency TKPKD, namely; First, the environment is still considered bad. This happens because there are still many individuals who are lazy to work. Second, there are still many organizations that are less active in working in the social sector, especially in terms of eradicating poverty. Third, the resources that West Pasaman Regency has in the TKPKD sector are still not optimal because West Pasaman has not fully maximized the resources that have been applied. Fourth, the character of the implementing agency: In this case, TKPKD implementers have not carried out their responsibilities well.